Evaluation of the Physical and Biological Properties of Ti-34Nb-6Sn/Mg Alloy Obtained by Powder Metallurgy for Use as Biomaterial - Rossi, Mariana Correa [UNESP] (2022)
Ti-34Nb-6Sn alloy were prepare by powder metallurgy milled in two different times (40 and 60 min) using Ti and Nb hydrides with or without Mg, as spacer then sintered at 700 degrees C and 800 degrees C. Characterizations were made by scanning electron microscope (SEM), X-ray diffractometer (XRD) and by Archimedes. Microhardness was measured by Vickers microhardness. Mesenchymal stein cells derived from equine bone marrow (BMMSCs) were used to evaluate the sample cytotoxicity. Hydration and dehydration process was confirmed, also the formation of brittle particles during the milling. Materials were structured under alpha and beta phase, and the samples that received Mg as a spacer had slightly lower beta phase content compared to samples without Mg, suggesting difficult alpha ->beta transformation due to the presence of barriers formed by pores. Mg provided greater porosity, and prepared milled in a shorter time promoted an increase in the macropores. Microhardness was similar to that of commercial materials (i.e., CP-Ti and also to other alloys with similar nominal composition. Cells treated with conditioned medium with the samples showed viability comparable to the control group, and after 48 h of culture on the samples, there was significant growth and more circular morphology, when adhered on materials that received Mg.